Hubungan Lingkungan Kerja dengan Komitmen Organisasi pada Kantor Desa Ugi Kecamatan Sabbangparu Kabupaten Wajo - Mashra Karateng; Muktmir Usman; Syupriadi Syupriadi; Andi Anugrah (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
This research was carried out at the Ugi Village Office, Sabbangparu District, Wajo Regency. The implementation of the research will start from March to June 2024. This study aims to find out the working environment of employees at the Ugi Village Office, Sabbanparu District, Wajo Regency, to find out the organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency, and to find out the relationship between the work environment and organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency. The method used is a census type with a quantitative associative approach.The results of this study show that the work environment carried out at the Ugi Kacamatan Sabbangparu Village Office, Wajo Regency, has a value of 297 and is included in the category of both the average ideal value in the dimensions of the physical work environment and the non-physical work environment. The organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency is included in the good category with a score of 361 from the average ideal value. This is seen from the dimension of organizational commitment based on personalization, job characteristics, structural characteristics and work experience. To find out the work environment is positively and significantly related to the organization's commitment to the Ugi Village Office, Sabbangparu District, Wajo Regency.